Investigation of Factors That Affect the Quality of Life After a Stroke - Malliarou, Maria; Tsionara, Christina; Patsopoulou, Anna; Bouletis, Axilleas; Tzenetidis, Vasileios; Papathanasiou, Iokasti; Kotrotsiou, Evangelia; Gouva, Mary; Nikolentzos, Athanasios; Sarafis, Pavlos (My University, 2023)
Stroke, as a disease, describes a group of disorders characterized by the presence of central nervous system symptoms either as a result of ischemia (ischemic stroke) or bleeding (hemorrhagic stroke). The appearance of a stroke results in a permanent physical or cognitive disability. The stroke incidence is the third cause of death after heart disease and cancer, and is the main cause of long-term disability.The effects of a stroke on a patient's daily life, and hence on his quality of life, are intense and long-lasting. These include memory problems, speech difficulty, depression, reduced vision loss, and decreased walking ability. This limitation of the patient's motor activity has a direct negative impact on the quality of his life.To investigate the degree of this impact, a research was carried out at a hospital of Central Greece. The total sample consisted of 90 patients and the responses showed that post-stroke symptoms are significant. Consequences and treatment control of the disease on the life of the sample were the questions with the highest score showing the significant effect that a stroke has on life the patients.More specifically, the sample showed through responses that the disease affects their lives to a great extent. The pre-stroke scores on the domains of the sample are clearly higher than post-stroke. The highest difference was found in the use of the upper extremities in self-care and family roles while the lowest was found in the domain of thinking. The most affected domains were as follows: thinking, vision, and language. Alternatively, the least affected domain was family roles.
Keywords: Illness Perception Questionnaire; Quality of life; Stroke